Stimulant Medication for ADHD: The Child's Perspective - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The knowledge and attitudes of children receiving stimulant medication for attention deficit hyperactivity disorder were investigated at the Division of Ambulatory Pediatrics, Children's Hospital, Boston, MA.